ADVANCE: An effective and feasible technique in acute stroke treatment - Gurkas, Erdem; Akpinar, Cetin Kursad; Aytac, Emrah (Sage Publications Inc, 2017)
Background and purpose: Different techniques regarding efficient utilization of thrombectomy devices have been reported. Here, we described a novel technique named ADVANCE that is based on advancing a distal access catheter over the stent retriever. In this study, we aimed to report our initial results with this novel thrombectomy technique. Methods and results: Sixty-seven consecutive acute anterior circulation ischemic stroke patients (35 male, 32 female) between January 2015 and January 2016 who were treated by mechanical thrombectomy were included in this prospective study. Patients were classified randomly into two groups: patients treated with either the ADVANCE technique or standard technique. Patients had a mean age of 61.1 +/- 12.9 years. The average NIHSS score was 15.8 +/- 3.8. In the ADVANCE group, the successful revascularization (mTICI 2b-3) rate was 87.1% and the 90-day good functional outcome rate (mRS 0-2) was 74.1%. The revascularization rate in the ADVANCE group was significantly (p = 0.005) better than the standard technique group and good functional outcome at 90 days in the ADVANCE group was non-significantly better than the standard technique group (p = 0.052). Conclusions: ADVANCE is the first comparison of this technique to standard stent retriever thrombectomy with a higher rate of revascularization with no emboli to new territory and fewer distal emboli to target territory. This safe and efficient technique needs to be validated in large patient series in new thrombectomy trials.
Keywords: Acute stroke; ADVANCE technique; interventional neurology; mechanical thrombectomy; novel technique